Answer

Verified

448.5k+ views

Hint: In this problem we have been with a triangle ABC such that the line segment DE inside this triangle is parallel to BC. So BCED forms a trapezium now and it is given that this DE divides this triangle into two equal areas. Thus use the respective formula for area of triangle and area of trapezium along with triangle congruence postulates to reach the answer.

Complete step-by-step answer:

It is given that the area of triangle ADE is equal to the area of trapezium BCED.

$ \Rightarrow {\text{Area}}\left( {\Delta ADE} \right) = {\text{Area}}\left( {{\text{trapezium BCED}}} \right)$

Now add area of triangle ADE both sides we have

$ \Rightarrow {\text{Area}}\left( {\Delta ADE} \right) + {\text{Area}}\left( {\Delta ADE} \right) = {\text{Area}}\left( {\Delta ADE} \right) + {\text{Area}}\left( {{\text{trapezium BCED}}} \right)$

In above equation R.H.S part is the total area of triangle ABC

\[ \Rightarrow 2{\text{Area}}\left( {\Delta ADE} \right) = {\text{Area}}\left( {\Delta ABC} \right)\]

\[ \Rightarrow \dfrac{{{\text{Area}}\left( {\Delta ADE} \right)}}{{{\text{Area}}\left( {\Delta ABC} \right)}} = \dfrac{1}{2}\] …………………. (1)

Now in triangle ADE and in triangle ABC we have

$\angle ADE = \angle B$ [$\because DE||BC{\text{ & }}\angle ADE = \angle B$ (Corresponding angles)]

And, $\angle A = \angle A$ [common angle]

Therefore \[{\text{Area}}\left( {\Delta ADE} \right) \approx {\text{Area}}\left( {\Delta ABC} \right)\] (similar triangles)

Therefore according the property of similar triangles

$\dfrac{{AD}}{{AB}} = \dfrac{{AE}}{{AC}} = \dfrac{{DE}}{{BC}} = \sqrt {\dfrac{{{\text{Area}}\left( {\Delta ADE} \right)}}{{{\text{Area}}\left( {\Delta ABC} \right)}}} $

Now from equation (1) we have

$\dfrac{{AD}}{{AB}} = \dfrac{{AE}}{{AC}} = \dfrac{{DE}}{{BC}} = \sqrt {\dfrac{1}{2}} = \dfrac{1}{{\sqrt 2 }}$

$ \Rightarrow AD = \dfrac{{AB}}{{\sqrt 2 }}$……………………………. (2)

Now from figure we can say that

$BD = AB - AD$

Now from equation (2)

$BD = AB - AD = AB - \dfrac{{AB}}{{\sqrt 2 }}$

$ \Rightarrow \dfrac{{BD}}{{AB}} = 1 - \dfrac{1}{{\sqrt 2 }}$.

So, this is the required ratio of BD to AB.

Thus, this is the required answer.

Note: Whenever we face such types of geometry questions the key point is to understand the diagrammatic representation of the data provided in the question. Having a good understanding of various triangle congruence postulates like ASA, AAA, SSS along with formulas of various sections like triangle and trapezium always helps in getting on the right track to reach the answer.

Complete step-by-step answer:

It is given that the area of triangle ADE is equal to the area of trapezium BCED.

$ \Rightarrow {\text{Area}}\left( {\Delta ADE} \right) = {\text{Area}}\left( {{\text{trapezium BCED}}} \right)$

Now add area of triangle ADE both sides we have

$ \Rightarrow {\text{Area}}\left( {\Delta ADE} \right) + {\text{Area}}\left( {\Delta ADE} \right) = {\text{Area}}\left( {\Delta ADE} \right) + {\text{Area}}\left( {{\text{trapezium BCED}}} \right)$

In above equation R.H.S part is the total area of triangle ABC

\[ \Rightarrow 2{\text{Area}}\left( {\Delta ADE} \right) = {\text{Area}}\left( {\Delta ABC} \right)\]

\[ \Rightarrow \dfrac{{{\text{Area}}\left( {\Delta ADE} \right)}}{{{\text{Area}}\left( {\Delta ABC} \right)}} = \dfrac{1}{2}\] …………………. (1)

Now in triangle ADE and in triangle ABC we have

$\angle ADE = \angle B$ [$\because DE||BC{\text{ & }}\angle ADE = \angle B$ (Corresponding angles)]

And, $\angle A = \angle A$ [common angle]

Therefore \[{\text{Area}}\left( {\Delta ADE} \right) \approx {\text{Area}}\left( {\Delta ABC} \right)\] (similar triangles)

Therefore according the property of similar triangles

$\dfrac{{AD}}{{AB}} = \dfrac{{AE}}{{AC}} = \dfrac{{DE}}{{BC}} = \sqrt {\dfrac{{{\text{Area}}\left( {\Delta ADE} \right)}}{{{\text{Area}}\left( {\Delta ABC} \right)}}} $

Now from equation (1) we have

$\dfrac{{AD}}{{AB}} = \dfrac{{AE}}{{AC}} = \dfrac{{DE}}{{BC}} = \sqrt {\dfrac{1}{2}} = \dfrac{1}{{\sqrt 2 }}$

$ \Rightarrow AD = \dfrac{{AB}}{{\sqrt 2 }}$……………………………. (2)

Now from figure we can say that

$BD = AB - AD$

Now from equation (2)

$BD = AB - AD = AB - \dfrac{{AB}}{{\sqrt 2 }}$

$ \Rightarrow \dfrac{{BD}}{{AB}} = 1 - \dfrac{1}{{\sqrt 2 }}$.

So, this is the required ratio of BD to AB.

Thus, this is the required answer.

Note: Whenever we face such types of geometry questions the key point is to understand the diagrammatic representation of the data provided in the question. Having a good understanding of various triangle congruence postulates like ASA, AAA, SSS along with formulas of various sections like triangle and trapezium always helps in getting on the right track to reach the answer.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

How many crores make 10 million class 7 maths CBSE

The 3 + 3 times 3 3 + 3 What is the right answer and class 8 maths CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE